QOL-36. QUALITY OF SURVIVAL IN SIOPE BRAIN TUMOUR CLINICAL TRIALS FOR CHILDREN AGED LESS THAN 5 YEARS: DEVELOPMENT OF A CLINICAL TRIAL PROTOCOL. Issue 2 (22nd June 2018) - Limond, Jenny; Thomas, Sophie; Bull, Kim; Lemiere, Jurgen; Traunwieser, Thomas; Spoudeas, Helen; Van Santen, Hanneke M; Weiler-Wichtl, Liesa; Lüttich, Peggy; Calaminus, Gabriele; Chevignard, Mathilde
Abstract: There is international recognition of the need to assess quality of survival (QoS) in children treated for brain tumours. Further to the work of the QoS working group of the European Society of Paediatric Oncology (SIOPE) Brain Tumour group and the Core 'plus' model of QoS assessment in clinical trials for children aged 5-18 years (Limond et al., 2015), the group has established a consensus for QoS assessment for children aged <5 years. Similar to older children, areas of assessment discussed include core medical domains (e.g. vision, hearing, mobility, endocrine), emotion, behaviour, adaptive behaviour, and cognitive functioning. Issues highlighted for this younger age group include reliability and validity of infant and young child measures, predictive value of early measures, and compatibility of measures across countries and age groups. Nevertheless the QoS group has agreed a hierarchy of neuropsychological assessments to maximise data collection to enable statistical analyses of these data in a larger number of patients than had previously been possible. As with the 5-18 year consensus, a Core 'plus' approach is suggested in which core assessments (direct and indirect tests) are recommended for all clinical trials. The core component is a brief screening assessment that, in most countries, is a sub-component of routine clinical provision and therefore achievable even where specific resources for QoS assessment are unavailable. The 'plus' component enables the addition of assessments which can be selected for tumour-, age-, and location-specific groups in order to enhance the overview of specific medical, cognitive and other relevant domains.